Oportunisme, Konflik, dan Dualitas Kepuasan dalam Hubungan Bisnis Beton Precast - Holidin Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to observe the role of opportunism and conflict on dual satisfaction, namely non-economic satisfaction and economic satisfaction, as well as its implications on the intention to maintain business relationships in the precast concrete industry from the buyer's perspective. The precast concrete industry in Indonesia is a business-to-business (B2B) sector that is highly dependent on the sustainability of business relationships, especially in an increasingly price-driven and project-based competitive environment. This study uses a quantitative approach through questionnaires. Data were obtained from 175 respondents representing buyer companies in the precast concrete industry in Indonesia. The sampling technique used was purposive sampling. Data analysis was performed using Structural Equation Modeling (SEM) through AMOS 26 software. The results show that seller opportunism has a significant positive effect on conflict. Furthermore, neither seller opportunism nor conflict has a significant effect on buyer non-economic satisfaction. Non-economic satisfaction has been proven to have a significant positive effect on economic satisfaction. Furthermore, non-economic satisfaction and economic satisfaction have a significant positive effect on buyers' intention to maintain business relationships in the precast concrete industry. These findings indicate that in the context of the construction industry, with a majority of male respondents who tend to be masculine, conflict and opportunistic behavior by sellers tend to be perceived as part of the professional dynamics of the project, thus not directly reducing the non-economic satisfaction of buyers. Nevertheless, non-economic aspects still play an important relational role as they form the basis for economic satisfaction and encourage buyers' intention to maintain long-term business relationships.